2020
DOI: 10.1002/jsfa.10720
|View full text |Cite
|
Sign up to set email alerts
|

Rumen bacteria and meat fatty acid composition of Sunit sheep reared under different feeding regimens in China

Abstract: BACKGROUNDRumen bacteria play a critical role in feed degradation and productivity. This study evaluated the impact of feeding regimen on the rumen microbial populations and fatty acid composition of the meat of sheep. Twenty‐four Sunit sheep were raised on a grass pasture from birth to 9 months of age, at which time they were randomly divided into two feeding groups: pasture feeding (PF) and barn feeding (BF). Sheep in the PF group were allowed to graze freely on wild grassland for 3 months. Sheep in the BF g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 57 publications
3
18
0
Order By: Relevance
“…We found the increased abundance of ruminal Butyrivibrio_2 in the G group lambs compared to the F group, and we found that the ruminal Butyrivibrio_2 was highly correlated with meat acetylcarnitine. It was reported that the meat C18:3n3 and conjugated linoleic acid contents were positively correlated with the abundance of ruminal Butyrivibrio_2 . Besides, Anaerovorax may also be involved in the ruminal response in biohydrogenation .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found the increased abundance of ruminal Butyrivibrio_2 in the G group lambs compared to the F group, and we found that the ruminal Butyrivibrio_2 was highly correlated with meat acetylcarnitine. It was reported that the meat C18:3n3 and conjugated linoleic acid contents were positively correlated with the abundance of ruminal Butyrivibrio_2 . Besides, Anaerovorax may also be involved in the ruminal response in biohydrogenation .…”
Section: Discussionmentioning
confidence: 99%
“…Tan lamb, high-quality meat with lower “off-flavor” and “mutton smell,” is mainly distributed in the Ningxia Hui Autonomous Region of China, which previously grazed a lot but now is raised with different production strategies . Feeding regimes with pasture feeding or barn feeding showed remarkable differences in the meat FA profiles of Sunit sheep . It was found that grazing systems are very profitable for lamb meat quality, have lower cost concerning inputs, and are more sustainable, but they usually have poor production performances .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same way, a larger ellipse that we could notice for family farming practices indicates a greater variability found in the resistome from the extensive method that is applied to those animals. Therefore, the type of regimen seems to be directly involved with the construction of the resistome, as the loss of diversity and uniformity in microbial communities are already widely discussed when confinement is practiced ( Wang et al., 2021 ). However, it is known that in family farming environments, there are several interactions between different animal species, which can be another collaborative factor for the greater heterogeneity between samples in this group.…”
Section: Discussionmentioning
confidence: 99%